Extending Access, Choice, and the Reign of the Market: Higher Education Reforms in British Columbia, 1989-2004 - Dennison, John D.; Schuetze, Hans G. (Canadian Journal of Higher Education, 2004)
British Columbia has implemented two significant higher education reforms in the last 15 years. The first was an Access for All policy, and in particular, the creation of a new breed of institution—university colleges—and recognition of the right of colleges and institutes to confer "applied" degrees. The second reform, more recent and potentially with wider effect, is the decision to allow and, in fact, encourage the emergence of a private higher education sector to complement and to compete with the public sector. Although both reforms had the declared objective of enhancing accessibility and choice by expanding opportunities to study for degrees, the more recent one, now being implemented, had the further objective of opening higher education to market forces.